Transcriptome Analysis Reveals the Anti-cancerous Mechanism of Licochalcone A on Human Hepatoma Cell HepG2 - Wang, Jun; Wei, Bo; Thakur, Kiran; Wang, Chu-Yan; Li, Ke-Xin; Wei, Zhao-Jun (Frontiers in Nutrition, 2021)
Hepatocellular carcinoma is a malignancy with a low survival rate globally, and there is imperative to unearth novel natural phytochemicals as effective therapeutic strategies. Licochalcone A is a chalcone from Glycyrrhiza that displayed various pharmacological efficacy. A globally transcriptome analysis was carried out to reveal the gene expression profiling to explore Licochalcone A's function as an anti-cancer phytochemical on HepG2 cells and investigate its potential mechanisms. Altogether, 6061 dysregulated genes were detected (3414 up-regulated and 2647 down-regulated). SP1 was expected as the transcription factor that regulates the functions of most screened genes. GO and KEGG analysis was conducted, and the MAPK signaling pathway and the FoxO signaling pathway were two critical signal pathways. Protein-protein interaction (PPI) network analysis based on STRING platform to discover the hub genes (MAPK1, ATF4, BDNF, CASP3, etc.) in the MAPK signaling pathway and (AKT3, GADD45A, IL6, CDK2, CDKN1A, etc.) the FoxO signaling pathway. The protein level of essential genes that participated in significant pathways was consistent with the transcriptome data. This study will provide an inclusive understanding of the potential anti-cancer mechanism of Licochalcone A on hepatocellular, signifying Licochalcone A as a promising candidate for cancer therapy.